Sunday
March 26, 2017

Post a New Question

Posted by on .

3n/(n2 -7n + 10) - 2n/(n2-8n+15)

  • algebra 2 - ,

    First factor the denominators.


    3n/(n^2 -7n + 10) - 2n/(n^2-8n+15)
    = 3n/[(n-5)(n-2)] -2n/[(n-5)(n-3)]

    = [n/(n-5)] *{[3/(n-2)]-[2/(n-3)]}
    = [n/(n-5)] *{[3(n-3)-2(n-2)/(n-2)(n-3)]}
    = [n/(n-5)]*(n+5)/[(n-2)(n-3)]
    This does not seem to be getting any simpler.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question